Surveilling the Mind and Body: Medicalising and De-medicalising Homosexuality in 1970s New Zealand - Bennett, James E. (Med Hist, 2018)
‘Medicalisation’ of same sex relations is a phenomenon that reached its peak in the 1950s and 1960s. The rise of gay liberation produced a divisive political contest with the psychiatric profession and adherents of the orthodox ‘medical model’ in the United States and – to a lesser extent – in the United Kingdom. This socio-historical process occurred throughout the English-speaking world, but much less is known about its dynamics in smaller countries such as New Zealand where the historiography on this issue is very sparse. The methodology situates New Zealand within a transnational framework to explore the circulation of medical theories and the critical responses they were met with. The article is anchored around three key local moments in the 1970s to consider the changing terrain on which ideas about homosexuality and psychiatry were constantly rearranged during this decade. This power struggle took a number of twists and turns, and the drive toward medicalisation alternated with a new impetus to de-medicalise same-sex sexuality.